Pengaruh Likuiditas Dan Kualitas Aset terhadap Profitabilitas pada Bank Umum Nasional (Studi pada Bursa Efek Indonesia Periode 2010-2014) - Daniel Siahaan; Nadia Asandimitra (BISMA (Bisnis dan Manajemen), 2018)
This study exmines the factors that affect the profitability of the national commercial banks. This study used data 32 commercial banks that go pulic in Indoesia Stock Exchange period 2010-2014. Sampling was done by purposive sampling method. This study used multiple linear regression analysis using SPSS 20. Independent variable of this study is Liquidity (LDR) and Asset Quality (NPL).The results of the study explain that Liquidity is a positive effects on Profitability. Liquidity be a measure of the success a bank to obtain high profitability. The lower the LDR reflects the bank has not been able to optimize third-party funds (DPK), which will be distributed to customers as a credit. Asset Quality negatively affect Profitability. High-Quality assets in a bank means more credit problems experienced by banks and will result in losses in the bank.